2022
DOI: 10.1021/acs.jafc.2c00276
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Constitutive Stilbenoid Levels and Profiles in Grape Cane (Vitis vinifera L.) Depending upon Variety and Clone, Location in the Vineyard, Pruning Time, and Vintage

Abstract: Stilbenoids in grape cane (Vitis vinifera L.) are bioactive compounds relevant for plant defense and the potential valorization of this byproduct. Our screening of grape cane from 102 varieties showed constitutive stilbenoid levels in a wide range (557−7748 mg/kg of dry weight). Analyses of genetically distinct clones of selected cultivars unraveled that intravarietal variability (e.g., cv. Riesling, 3236−6541 mg/kg) was higher than that across samples from a single clone but different vineyard positions (3017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Malbec in both matrices. ,, A recent study proved that PC richness was vine variety-dependent, varying by a 4-fold factor for a large collection of European grape cultivars . Some authors reported that stems of red grape varieties had higher content of proanthocyanidins, flavonols, hydroxycinnamic acids, anthocyanins, and stilbenes than those of white varieties. , In a comprehensive screening of grape canes from 102 varieties, Besrukow et al showed the qualitative and quantitative variability of constitutive stilbenoids. They observed that red grape wine varieties presented in average a little higher concentration of stilbenes.…”
Section: Factors Affecting Qualitative and Quantitative Composition O...mentioning
confidence: 99%
See 2 more Smart Citations
“…Malbec in both matrices. ,, A recent study proved that PC richness was vine variety-dependent, varying by a 4-fold factor for a large collection of European grape cultivars . Some authors reported that stems of red grape varieties had higher content of proanthocyanidins, flavonols, hydroxycinnamic acids, anthocyanins, and stilbenes than those of white varieties. , In a comprehensive screening of grape canes from 102 varieties, Besrukow et al showed the qualitative and quantitative variability of constitutive stilbenoids. They observed that red grape wine varieties presented in average a little higher concentration of stilbenes.…”
Section: Factors Affecting Qualitative and Quantitative Composition O...mentioning
confidence: 99%
“…In fact, stilbene synthesis in berries caused by gray mold ( Botrytis cinerea ) is favored by moderate humidity conditions, while it is not so much in dry conditions . Besrukow et al reported that the variability of stilbenoids levels in grape cane was affected by environmental factors in the different years of study. Indeed, nearly to 35% less concentration of trans -ε-viniferin in cv .…”
Section: Factors Affecting Qualitative and Quantitative Composition O...mentioning
confidence: 99%
See 1 more Smart Citation
“…49 Grape canes have been shown to contain high amounts of stilbenoids with total contents of 2.4 to 5.8 g/kg DW, though stilbenoid concentration is highly dependent on the subspecies, the cultivar, the environment, and the pruning time. 47,50,51 A recent study has investigated the abundance of stilbenoids in vine shoots from 23 Italian varieties and described varying contents ranging between 2.7 and 6.4 g/kg. 52 The data gathered in Table 1 also indicate that the distribution of stilbenoids significantly differs between plant tissues.…”
Section: Occurrence Of Stilbenoids In Crop and Forest Byproductsmentioning
confidence: 99%
“…For example, in Francethe world’s third largest producer of grapes approximately 1.8 million tons of grape canes and grapevine stocks are estimated to be wasted each year . Grape canes have been shown to contain high amounts of stilbenoids with total contents of 2.4 to 5.8 g/kg DW, though stilbenoid concentration is highly dependent on the subspecies, the cultivar, the environment, and the pruning time. ,, A recent study has investigated the abundance of stilbenoids in vine shoots from 23 Italian varieties and described varying contents ranging between 2.7 and 6.4 g/kg . The data gathered in Table also indicate that the distribution of stilbenoids significantly differs between plant tissues. A noteworthy discovery by Gabaston et al was that the degree of oligomerization of stilbenoids progressively increased from upper to underground parts of grapevine plants (Figure ).…”
Section: Stilbenoids: Physicochemical and Biological Properties And O...mentioning
confidence: 99%